Relation of IL-1β, IL-5, IL-6 and IL-8 with stable angina pectoris - Hamza A. Khalid; Mahdi M. Thuwaini; Ali Esmail Al-Snafi (University of Thi-Qar Journal of Science, 2023)
The inflammatory mediators released by injured endothelium enhance the interaction of circulating leukocytes with endothelial cells and contribute to development and progression of atherosclerosis. In this study we designed to determine some interleukins (IL-1β, IL-5, IL-6 and IL-8) as diagnostic markers instable angina pectoris.Methods: The study was carried out on 30 patients who were diagnosed with stable angina pectoris (18 males and 12 females).They visited Nasiriya Heart Center throughout the period from the beginning of November 2021 to the end of April 2022, and 20 age matched healthy person (13 males and 7 females). IL-1β, IL-5, IL-6, IL-8 were assayed by an enzyme-linked immunosorbent assay (ELISA). Troponin I (cTnl) was determined by using monoclonal cTnI-specific antibody. D- dimer by electro-chemiluminescence method. CK-MB by monoclonal CK-MB-specific antibody. Myoglobin by monoclonal MYO-specific antibody.Results: Male and female patients with stable angina showed significantly elevated serum levels of troponin (P<0.001), D-dimer (P<0.001) and (P<0.01) respectively, CK-MB (P<0.01), myoglobin (P<0.01), IL-1β (P<0.01 and <0.05 respectively) and IL-6 (P<0.05), with non-significant changes in the levels of IL-5 and IL-8 in comparison with healthy male and female individuals respectively.Conclusion: In addition to troponin, D-dimer, CK-MB and myoglobin; the proinflammatory mediators such as IL-1β, and IL-6 are helpful diagnostic markers instable angina pectoris.